Cellulose production by Gluconacetobacter kakiaceti GM5 in two batch process using vinasse as culture media (2015)
ABSTRACT: The present study was conducted to evaluate the cellulose production by Gluconacetobacter kakiaceti GM5 by means of two aerobic treatments: the static discontinuous fermentation process (treatment 1) and the discontinuous fermentation process in a rotary shaker (treatment 2). All these experiments were carried out using vinasse as experimental culture media (VM) and were compared with standard media containing glucose at 2% (standard medium (SM)). A sample of each treatment was extracted every 24 h over a period of 168 h. The maximum rates of cellulose produced in treatment 1 using SM added up to 3.63 ± 0.18 g l 1, and to 4.15 ± 0.16 g l 1 when VM was used. The amount of cellulose produced in treatment 2 using SM was 2.95 ± 0.09 g l 1 (which suggests an increase of 37%), and added up to 1.84 ± 0.07 g l 1 when using VM. A better global yield of both treatments in terms of sugar consumption after 168 h was obtained when using VM: 32% in treatment 1, whereas in treatment 2 it was 9%. A 20% decrease on vinasse COD (Chemical Oxy